Proyecto de factibilidad para la creación de una empresa productora y comercializadora de helados a base de yogurt (queso y manjar) en la ciudad de Loja - Agurto Peñarreta, Osmara Bristney (2024)
The present work was elaborated with the purpose of determining the financial viability for a “Feasibility project for the creation of a yogurt-based ice cream (cheese and manjar) production and marketing company in Loja city”, which seeks to satisfy the needs of families through a quality product with a nutritional value and at an accessible cost. The purpose of this project was to carry out the execution of the objectives, such as the market study, which allowed us to analyze the supply and demand; also accompanied by the technical, legal and administrative study to determine the technical feasibility of the location, project engineering and organizational design, which must meet the legal requirements for proper operation, also includes the study and financial evaluation, which allowed us to know the investment budget and get to know the feasibility of the project. The methodology used for this project was: quantitative and qualitative research approach, as well as methods (exploratory-descriptive) and techniques such as bibliographic compilation, surveys and interviews. A market study was conducted, within the results obtained from the surveys conducted both to the demanders and suppliers, allowed an analysis of supply and demand, therefore, it was determined that, for year one there is an effective demand of 86% of yogurt-based ice cream (cheese and manjar) and a supply of 21,094.00, thus obtaining the unsatisfied demand, being this of 4,964,915 units of ice cream for the first year. Next, the technical study was developed, in which the size of the plant is presented in correlation to the installed and used capacity of the company for the production of yogurt-based ice cream (cheese and manjar), the macro and micro location was defined. The company will be established in the city of Loja, in the parish of San Sebastian, this sector is strategic, and it is very accessible for the citizens to acquire the product that is being offered. In the organizational study, it was determined that the yogurt- based ice cream production and marketing company will be legally constituted, and the functional and positional structure was established, as well as the proposed functions manual, which will have a minimum duration of 5 years. The financial study provided information on the project's investment of US$29,389.87, which will be financed with 15% equity and 85% of the loan from BanEcuador, at an annual interest rate of 11.25%. The unit cost of production for the first year will be 0.58 cents, plus a 20% profit margin, resulting in a retail price of 0.69 cents, yielding $112,093.03 in sales revenue for the first year. For the evaluation of the project, indicators such as the Net Present Value (NPV) were analyzed, which is $34,692.66, making the project acceptable since it is greater than the initial investment; the internal rate of return (IRR) is 44.35%, with a 20 benefit-cost ratio of $1.29. The sensitivity analysis shows positive results of 0.97 and 0.99, allowing the project to be developed. Finally, conclusions and recommendations are made, detailing that the project is positively viable and its development is recommended. Keywords: projects, supply, demand, investment, dairy, supply, consumers